Myths and symbols in Indian art and civilization - Zimmer, Heinrich Robert, 1890-1943 (Works by Heinrich Zimmer., 1972)
This book interprets for the Western mind the key motifs of India's legend, myth, and folklore, taken directly from the Sanskrit, and illustrated with seventy plates of Indian art. It is primarily an introduction to image-thinking and picture-reading in Indian art and thought, and it seeks to make the profound Hindu and Buddhist intuitions of the riddles of life and death recognizable not merely as Oriental but as universal elements.